Risk Factors for Women to Have Urodynamic Stress Urinary Incontinence at A Turkish Tertiary Referral Center: A Multivariate Analysis Study - Citgez, Sinharib; Onal, Bulent; Erdogan, Sarper; Demirdag, Cetin; Korkmaz, Merve; Demirkesen, Oktay; Talat, Zubeyr; Erozenci, Ahmet; Cetinel, Bulent (Urology Journal, 2015)
Purpose: To investigate the risk factors in women with urodynamic stress urinary incontinence (USTIC) at a Turkish tertiary referral center. Materials and Methods: The urodynamic records of 3038 consecutive women were analyzed between 1990 and 2011. The patients who had etiological factor of neurologic disease were excluded. There were 1187 women who had USTIC after urodynamic investigation and 274 women who had no incontinence symptoms were included in the study. Multivariate analyses were done using logistic regression test to determine the risk factors for USTIC. Results: The mean age was 50.1 years (range, 86-18). Increased age, vaginal delivery, cesarean section, anterior prolapse existence in physical examination, previous anti-incontinence surgery, and previous pelvic organ prolapse surgery was found to be significant risk factors for USTIC at multivariate analyses. Conclusion: There are risk factors for women to have USTIC. Increased age, having vaginal delivery, having cesarean section, anterior prolapse, previous anti-incontinence surgery and previous prolapse surgery were found to be risk factors for women to have USTIC at this study.